Factors Contributing to the Rise of Algerian Neighborhood Gangs - Bezaz , Ibrahim; Fettache, Nora (Journal of Human Sciences, 2023)
Neighborhood gang crimes have received a lot of attention recently because they present a significant challenge to the state’s efforts to promote security, stability, and sustainable development. With the help of theoretical research in the social and human sciences, we hope to locate this phenomenon through this study in order to diagnose, analyze, and come up with radical solutions for it. Additionally, by being aware of its historical roots, realistic, and fictional traits, contrasting it with other crimes of a similar nature, and attempting to count the crimes it commits. looking into what led to the emergence of such a criminal phenomenon in Algerian society and its causes and contributing factors. In addition to the many difficulties the Algerian institution is facing, the methods for punishing the members of these gangs and the mechanisms suggested to stop and prevent their growth.